2012
DOI: 10.1002/clen.201100469
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Phosphate by Biomass Char Deriving from Fast Pyrolysis of Biomass Waste

Abstract: Biomass char (BC) deriving from fast pyrolysis of biomass was a potential adsorption material due to its relative high fixed‐carbon content and the inherent porous structures. Adsorption of phosphate from aqueous solution by BC was investigated in this paper. The results showed that the adsorption capacity of BC was dependent on pyrolysis conditions, such as temperature and holding time. The maximum adsorption capacity for phosphate was approximately 15.11 mg g−1 at 298 K. The pseudo‐second order model of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(53 citation statements)
references
References 27 publications
3
49
0
1
Order By: Relevance
“…Similar results were found by Prapagdee and Tawinteung (2017), who reported no significant difference of P content in green bean parts at all BC treatments. Biochar can be a potential P source and some BC can also adsorb P efficiently from solutions (Peng et al 2012, Yao et al 2013. They suggested that BC could play a role in retaining P applied as fertilizer.…”
Section: Resultsmentioning
confidence: 99%
“…Similar results were found by Prapagdee and Tawinteung (2017), who reported no significant difference of P content in green bean parts at all BC treatments. Biochar can be a potential P source and some BC can also adsorb P efficiently from solutions (Peng et al 2012, Yao et al 2013. They suggested that BC could play a role in retaining P applied as fertilizer.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, biochar production, focused on agricultural residues, has gained increasing interest [1][2][3]. Biochar is a recalcitrant organic compound and better environmental improvement additive, created when biomass (feedstock) is heated to temperatures between 300 and 10008C under low oxygen concentrations [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the cost of water treatment will be reduced . Eventually, by converting waste into fertilizers and useful materials for water treatment, this practice may create revenues (Huang et al 2010;Peng et al 2012). Apparently it may provide a sustainable, efficient and profit regenerating solution for P management (Kuzma 2011).…”
Section: Dissolved Phosphorus (Organic)mentioning
confidence: 99%